Caveolae and caveolin-1 are implicated in 1α,25(OH)2-vitamin D3-dependent modulation of Src, MAPK cascades and VDR localization in skeletal muscle cells - Buitrago, Claudia Graciela (2010)
We previously reported that 1α,25(OH)2D3 induces non-transcriptional rapid responses through activation of MAPKs in C2C12 skeletal muscle cells. However, there is little information on the molecular mechanism underlying the initiation of 1α,25(OH)2D3 signaling through this pathway. Plasma membrane components have been involved in some non-genomic effects. In this work, we investigated the role of caveolae and caveolin-1 (cav-1) in 1α,25(OH)2D3-stimulation of c-Src and MAPKs. When proliferating cells were pretreated with methyl beta cyclodextrin (MβCD), a caveolae disrupting agent, under conditions in which cell morphology is not affected and no signs of apoptosis are observed, 1α,25(OH)2D3-dependent activation of ERK1/2, p38 MAPK and c-Src was suppressed. Similar results were obtained by siRNA technology whereby silencing of cav-1 expression abolished activation of c-Src and MAPKs induced by the hormone. By confocal immunocytochemistry it was observed that cav-1 colocalizes with c-Src in the periplasma membrane zone at basal conditions. Hormone treatment disrupted the colocalization of these proteins and redistributed them into cytoplasm and nucleus. Co-immunoprecipitation assays corroborated these observations. Changes in VDR localization after 1α,25(OH)2D3 exposure were also investigated. Confocal microscopy images showed that the hormone induces VDR translocation to the plasma membrane, and this effect is abolished by MβCD. Altogether, these data suggest that caveolae is involved upstream in c-Src-MAPKs activation by 1α,25(OH)2D3 and that VDR and cav-1 participate in the rapid signaling elicited by the hormone.